(1436) التفاوتات الإقليمية واستراتيجيات التنمية الإقليمية: التحضر على المستوى الإقليمى ومدى ارتباطه ببعض المؤشرات الاقتصادية Regional disparities and regional development strategies: Urbanization at the regional level and its relationship to certain economic indicators - عزيزة عبد العزيز سليمان (معهد التخطيط القومي, 2026)
تناقش هذه الدراسة العلاقة بين معدلات التحضر( انتقال السكان من الريف إلى المدن) ونوعية الحياة في محافظات مصر، مع التركيز على بيانات عام 1976 ، تهدف الباحثة إلى قياس مدى ارتباط التحضر بمؤشرات ديموجرافية واجتماعية واقتصادية محددة، مثل معدلات المواليد والوفيات، وتوفر الخدمات الأساسية كالمياه والكهرباء، وهيكل العمالة في القطاعات المختلفة، وذلك لفهم العوامل التي تجعل المدن مراكز جذب للسكان رغم ما تعانيه من مشكلات الزحف العمراني وتدهور الخدمات، وأظهرت نتائج التحليل الإحصائي وجود ارتباط قوي بين ارتفاع نسبة التحضر وتحسن جودة المسكن (توفر المياه النقية والكهرباء) وتنوع فرص العمل في القطاعين العام والخاص والخدمات، وتخلص الدراسة إلى أن تدني مستوى الخدمات في الريف هو المحرك الأساسي للهجرة نحو المدن، مما أدى لظهور مشكلات مثل "الصدمة الحضرية" وترييف هوامش المدن؛ لذا توصي بضرورة توجيه الاستثمارات لتطوير المناطق الريفية ورفع مستوى المعيشة فيها للحد من ظاهرة "الزحف الوحشي" على العاصمة والمدن الكبرى. This study discusses the relationship between urbanization rates (population migration from rural to urban areas) and quality of life in the governorates of Egypt, focusing on 1976 data. The researcher aims to measure the extent to which urbanization is linked to specific demographic, social, and economic indicators, such as birth and death rates, the availability of basic services like water and electricity, and the structure of the workforce in different sectors. This is to understand the factors that make cities attractive centers for populations despite the problems of urban sprawl and deteriorating services. The results of the statistical analysis showed a strong correlation between the high rate of urbanization and the improvement of housing quality (availability of clean water and electricity) and the diversity of job opportunities in the public, private, and service sectors. The study concludes that the low level of services in rural areas is the main driver of migration to cities, which has led to the emergence of problems such as "urban shock" and the realization of the outskirts of cities. Therefore, it recommends the necessity of directing investments to develop rural areas and raise the standard of living in them to reduce the phenomenon of "unbridled sprawl" on the capital and major cities